From competition to social interaction: a mobile team-based competition approach to promoting students' professional identity and perceptions. Issue 2 (17th February 2023) - Liu, Chenchen; Wan, Ping; Hwang, Gwo-Jen; Tu, Yun-Fang; Wang, Youmei
ABSTRACT: For professional development programs, students' professional identity and learning perceptions and earning performances have been recognized as important educational objectives. Scholars have indicated that engaging students in social interactions facilitates their deep and diverse thinking, and hence to promoting their learning outcomes. However, in traditional instruction, students generally learn in an individual learning mode and hesitate to interact with peers and teachers. To address this problem, a mobile team-based competition approach to situate students in social interactions was proposed. To evaluate the effectiveness of the proposed approach, an experiment was conducted in a college curriculum design course. 88 students in a teacher education program participated in the experiment, including 42 in the experimental group learning with the proposed approach, and 46 in the control group learning with the conventional mobile individual competition approach. The results showed that the proposed approach outperformed the mobile individual competition approach in terms of learning attitude, collaborative learning tendency and professional identity. It is found that the students generally perceived the proposed learning approach to be an effective way to encourage knowledge sharing, promote collaboration awareness and improve learning attitudes and motivation.